The Effect of Announcing Private Offering Placement on Stock Exchange on Stock Returns in Amman Stock Exchange at Semi-Strong level(Jordan Case) (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: efficiency of Amman stock exchange; financing through stock issuance; statistical significance; its graph shows that Amman Stock Exchange